Pseudomonas fluorescens DN16 Enhances Cucumber Defense Responses Against the Necrotrophic Pathogen Botrytis cinerea by Regulating Thermospermine Catabolism - Zhu, Lin; Qian, Nana; Sun, Yujun; Lu, Xiaoming; Duan, Haiming; Qian, Lisheng (Frontiers in Plant Science, 2021)
Plants can naturally interact with beneficial rhizobacteria to mediate defense responses against foliar pathogen infection. However, the mechanisms of rhizobacteria-mediated defense enhancement remain rarely clear. In this study, beneficial rhizobacterial strain Pseudomonas fluorescens DN16 greatly increased the resistance of cucumber plants against Botrytis cinerea infection. RNA-Sequencing analyses showed that several polyamine-associated genes including a thermospermine (TSpm) synthase gene (CsACL5) and polyamine catabolic genes (CsPAO1, CsPAO5 and CsCuAO1) were notably induced by DN16. The associations of TSpm metabolic pathways with the DN16-mediated cucumber defense responses were further investigated. The inoculated plants exhibited the increased leaf TSpm levels compared with the controls. Accordantly, overexpression of CsACL5 in cucumber plants markedly increased leaf TSpm levels and enhanced defense against B. cinerea infection. The functions of TSpm catabolism in the DN16-mediated defense responses of cucumber plants to B. cinerea were further investigated by pharmacological approaches. Upon exposure to pathogen infection, the changes of leaf TSpm levels were positively related to the enhanced activities of polyamine catabolic enzymes including polyamine oxidases (PAOs) and copper amine oxidases (CuAOs), which paralleled the transcription of several defense-related genes such as pathogenesis-related protein 1 (CsPR1) and defensin-like protein 1 (CsDLP1). However, the inhibited activities of polyamine catabolic enzymes abolished the DN16-induced cucumber defense against B. cinerea infection. This was in line with the impaired expression of defense-related genes in the inoculated plants challenged by B. cinerea. Collectively, our findings unraveled a pivotal role of TSpm catabolism in the regulation of the rhizobacteria-primed defense states by mediating the immune responses in cucumber plants after B. cinerea infection.